E.C. Yaneza Interior Design and Furniture Manufacturer - Aguirre, Nerie; Chico, Paul.; Montoya, Luis.; Valmeo, Jimmy; Yaneza, Gary. (Diliman, Quezon City College of Engineering, 1988)
E.C. Yanez Interior Design manufacturers on an order-basis. Production process starts with the designing of the furniture as per specification, by the customer. The design is then brought to the woodshop for cutting and assembly. Half-finished product is then brought to the finishing area for varnishing. If needed, it is taken to the upholsterer. After inspection and adjustments, the furniture is ready for delivery. From what the group had observed while conducting the study, we can suggest several changes that can be made for a smoother running operation. Generally, there are four (4) main problem areas. The workflow-wherein the distances of work stations seem unlikeable, the assignment of jobs does not conform with the standards they set, and the work sequence lacks a few, important steps; the shop layout-wherein the space provided for each work area does not satisfy each workplace; materials handling and equipment-wherein there are no means of simplifying the task of bringing materials to the shop and the equipment they are now using seem not enough for maximum protection; and the working environment-wherein there is lack of maintenance and lack of necessary shop features for the improvement of working conditions.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis